Effect of progesterone on Candida albicans biofilm formation under acidic conditions: a transcriptomic analysis - Gonçalves, Bruna (2020)
Supplementary material related to this article can be found, in the online version, at doi: https://doi.org/10.1016/j.ijmm.2020.151414.